Analysis of Emergency Nursing Care for Mr. J Diagnosed with Intracerebral Hemorrhage with the Application of a 30-Degree Head-Up Position to Reduce Intracranial Adaptive Capacity in the Emergency Department of Ulin Regional Hospital - Novela, Nurwidya; Mohtar, M. Sobirin; Santoso, Bagus Rahmat (PROMOTOR, 2025)
Intracerebral Hemorrhage (ICH) is a type of Hemorrhagic Stroke caused by hypertension, old age, and poor lifestyle. ICH can result in increased intracranial pressure and even sudden death due to brain herniation. One way to reduce increased intracranial pressure is by applying a 30° head-up position. The purpose of this study is to obtain a general overview of Emergency Nursing Care for Mr. J with a medical diagnosis of Intracerebral Hemorrhage by applying a 30° head-up position to reduce Intracranial Adaptive Capacity. This study uses a descriptive qualitative method with a type of Single Experimental Case Study research with a Nursing Care approach. The instruments in this study include assessment sheets, 3S books, Nursing kits, and SOP sheets, with a sample size of 1 respondent. The results based on the case study conducted can be concluded that the implementation of the 30° head-up position in ICH patients with nursing problems of Decreased Intracranial Adaptive Capacity has not been resolved with the outcome of Increased ICP Management. This research is expected to be applied in hospitals to ICH patients experiencing nursing problems of Decreased Intracranial Adaptive Capacity.